Effectiveness of Supplement Apps on Human Auditory System as STEM-Based Learning Media to Enhance Junior High School Students’ Analytical Thinking Skills - Yazid, Muhammad Abdau; Marwoto, Putut (Unnes Science Education Journal, 2025)
The study aims to evaluate the effectiveness of STEM-based learning media, the Supplement Apps Human Auditory System, in enhancing students’ analytical thinking skills. This product was developed in Hypertext Markup Language (.html) and follows a quantitative quasi-experimental design with a pre-test posttest nonequivalent control group. The research involved 136 eighth-grade students from a state junior high school 2 Tengaran, Semarang Regency, selected through cluster random sampling to form experimental and control groups. The application integrates Learning Outcomes & Objectives, Materials, Simulations, and Interactive Evaluations and is accessible via https://sahas.nim.my.id/, enabling seamless distribution for instructional use. The paired sample t-test results indicate a statistically significant improvement, with a t-value of 11.92 and an average N-gain score of 0.30 (moderate category). These findings indicate that the Supplement Apps Human Auditory System learning media effectively enhances analytical thinking skills, making it a promising tool for STEM-based education in junior high schools.